Improving the Yield and Nutritional Quality of Forage Crops - Capstaff, Nicola M.; Miller, Anthony J. (Frontiers in Plant Science, 2018)
Despite being some of the most important crops globally, there has been limited research on forages when compared with cereals, fruits and vegetables. This review summarises the literature highlighting the significance of forage crops, the current improvements and some of future directions for improving yield and nutritional quality. We make the point that the knowledge obtained from model plant and grain crops can be applied to forage crops. The timely development of genomics and bioinformatics together with genome editing techniques offer great scope to improve forage crops. Given the social, environmental and economic importance of forage across the globe and especially in poorer countries, this opportunity has enormous potential to improve food security and political stability.